(untitled) (Journal of history, 2017)
The article discusses the role and place of diplomatic documents in a complex of historical sources, denoted the importance of this type of sources in the complex sources of general historical perspective. It is expected to conduct classification of diplomatic sources by type, designated a priority composition of diplomatic source spectrum. Some scientists predict a new relationship between a group of documents described in this article and their presence in the so-called international diplomatic - documentary environment for the classification of diplomatic documents. This environment could include both state and interstate documentary positions that affect the change of the system of priority between the types of diplomatic sources. This term is supposed to determine the characteristics of diplomatic sources as the historical evidence on the modern history and the impact of documentary environment in improvement of classification of main types on new possible positions of priority. The author comes to a conclusion about the place and role of diplomatic documents in a globalized world of historical documentation.